1982
DOI: 10.1002/pol.1982.180201112
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency and high‐frequency relaxations in dynamic electric birefringence of poly(γ‐benzyl‐L‐glutamate) in m‐cresol

Abstract: The dc component Δn of the electric birefringence of poly(γ‐benzyl‐L‐glutamate) in m‐cresol is measured under an ac electric field at frequencies from 0.5 Hz to 200 kHz for solutions covering the dilute and semidilute regions. The dispersion curve indicates that at low frequencies Δn decreases with increasing frequency (low‐frequency relaxation). For high‐molecular‐weight polymers at high concentration, Δn becomes negative at high frequency and its absolute value decreases with further increase in frequency (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 14 publications
8
49
0
Order By: Relevance
“…We should only mention that even for such systems the rate is not expected to follow the c -2 behavior of the Doi-Edwards model in the whole semidilute and concentrated regime, but rather a weaker c dependence (c -1 ) at low concentrations, and only for highly entangled solutions is the DE behavior reached. 14,18,22 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We should only mention that even for such systems the rate is not expected to follow the c -2 behavior of the Doi-Edwards model in the whole semidilute and concentrated regime, but rather a weaker c dependence (c -1 ) at low concentrations, and only for highly entangled solutions is the DE behavior reached. 14,18,22 …”
Section: Resultsmentioning
confidence: 98%
“…While the rotational diffusion coefficient, D r , initially predicted from the DE model 1 for rods in the semidilute region, was to exhibit a strong c dependence (D r /D r,0 ∼ c -2 ), it is now evident, from both experimental studies 11,14,18 and other theoretical models and simulations, 21,15,22 that a rather weaker c dependence is followed until, only at high concentrations, the DE prediction is reached. These theories involve recalculation of the cage size 15 or consideration of dynamic distortion of cages and finite thickness effects.…”
Section: Theoretical Backgroundmentioning
confidence: 91%
“…the fiber can freely rotate in arbitrary directions. According to some authors, 26,27 this estimate is too strictly limiting. Instead of the volume fraction occurring in Eq.…”
Section: Model Shapes and Concentration Regimes For Suspensions Of Elmentioning
confidence: 93%
“…[46][47][48] These studies revealed a strong process, which was attributed to the rotation of the a-helix as a rigid rod. The relaxation times had a t $ M 3 molecular weight dependence, which is consistent with the rigid rod model.…”
Section: Persistence Length Of A-helicesmentioning
confidence: 99%